O sistema de precisão de engrenagens cilíndricas com dentado em evolvente de círculo - Aplicação ao controlo do engrenamento radial - José Almacinha (1992)
The scope of the present communication is the current status of environmental engineering in Portugal. The different approaches concerning the environmental engineering courses available at undergraduate levels as well as some post-graduation studies are described. Furthermore, an analysis based on strengths, weakness, opportunities and trend issues regarding the environmental engineering profession in Portugal is presented.